Facile synthesis and electrochemical properties of conducting SrRuO3-RuO2 composite nanofibre mats - Hyun, Tae-Seon; Kim, Ho-Gi; Kim, Il-Doo (ELSEVIER SCIENCE BV, 2010)
This study reports the facile synthesis of highly conductive SrRuO3(SRO)-RuO2 composite nanofibre mats and their potential suitability for application in electrochemical capacitors as an active electrode material. SRO-RuO2/poly(vinyl acetate) composite nanofibre mats are electrospun on to a Au-coated SiO2/Si substrate and a Ti substrate, subsequently thermocompressed at 60 degrees C, and calcined at various temperatures (from 350 to 850 degrees C). The calcined SRO-RuO2 nanofibre mats exhibit porous morphologies and bundle shapes composed of multiple-fibrils with a nanoparticle diameter ranging from 20 to 50 nm. Single SRO-RuO2 nanofibre and multiple SRO-RuO2 nanofibre mats show high electrical conductivity of 476 and 40.8 S cm(-1), respectively. Pseudocapacitors using SRO-RuO2 nanofibre mats calcined at 350 degrees C exhibit a high specific capacitance of 192 F g(-1) at a scan rate of 10 mV s(-1). The superior capacitance retention (83.4%) of the SRO-RuO2 nanofibre mats is maintained even at rapid scan rate of 1000 mV s(-1). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: ONE-DIMENSIONAL NANOSTRUCTURES; RUTHENIUM OXIDE; THIN-FILMS; HYDROUS RUO2; SUPERCAPACITORS; NANOCOMPOSITES; ARCHITECTURE; CAPACITORS; NANOWIRES; NANOTUBES